Pertanggungjawaban Pemerintah terhadap petugas PPS dan KPPS sebagai korban penyelengaraan pemilihan umum - Faisal Adhyaksa (University of Merdeka Malang, 2020)
The general election of the Indonesian State are the largest democratic progress in the world. At years 2019, process of election was incident by implementation problems. The problem resulted in several victims of violence and even died. The National Election Commission, will at least take part in being responsible for this incident. This research used normative juridical methods. This method using fundamental normative and theories analyse. Aspects of legal liability are from criminal law, civil law, administration, and even from political liability. Some aspects of the law that cannot be prosecuted are criminal and political aspects, but on the other side they can be prosecuted in terms of civil and administrative consequences as a result of the juristic person of the state. Accountability from the realm of civilization is a form of absolute accountability. In the realm of state administration law the loss of enforcement of AAUPB is a serious concern in public management which is increasingly leaning towards the private style. There is a need for monitoring of the implementation of elections in Indonesia because of the enormous political power which only threatens law enforcement.How to cite item: Adhyaksa, F. (2020). Pertanggungjawaban Pemerintah terhadap petugas PPS dan KPPS sebagai korban penyelengaraan pemilihan umum. Jurnal Cakrawala Hukum, 11(1), 21-30. doi:https://doi.org/10.26905/idjch.v11i1.3530